2018
DOI: 10.1021/acs.energyfuels.8b02788
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Petroleum Products by Gel Permeation Chromatography Coupled Online with Inductively Coupled Plasma Mass Spectrometry and Offline with Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: We have examined the aggregation behavior of a typical atmospheric residue feedstock by gel permeation chromatography (GPC). The size profiles for compounds containing sulfur, vanadium, and nickel were determined online from elemental detection by inductively coupled plasma (ICP) mass spectrometry. Four fractions that vary in aggregation state were analyzed by positive atmospheric pressure photoionization (APPI) 9.4 T Fourier transform ion cyclotron resonance mass spectrometry (APPI FT-ICR MS). Results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 29 publications
7
52
0
Order By: Relevance
“…Figure 6A presents the intensity of 51 V as a function of the retention time in the GPC for VR, DAO 2, raffinate 1 and aromatic extract. The profile of vanadium-containing aggregates is trimodal for VR, as already observed for this kind of petroleum product [11,31]. As expected, HMW compounds containing 51 V were present in the VR sample (black line).…”
Section: Gpc-icp Hr Ms Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Figure 6A presents the intensity of 51 V as a function of the retention time in the GPC for VR, DAO 2, raffinate 1 and aromatic extract. The profile of vanadium-containing aggregates is trimodal for VR, as already observed for this kind of petroleum product [11,31]. As expected, HMW compounds containing 51 V were present in the VR sample (black line).…”
Section: Gpc-icp Hr Ms Resultssupporting
confidence: 80%
“…As in our previous works [9,11,31], the introduction system of the mass spectrometer used in this work is a modified DS-5 microflow total consumption nebulizer (CETAC, Omaha, NE, USA) mounted with a laboratory-made glass spray chamber already used during prior study [31][32][33]. The temperature was maintained at 60 • C using a temperature-controlled bath with water (Neslab RTE-111, Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Gpc Icp Hr Msmentioning
confidence: 99%
“…The column calibration was only used to verify the performance of the columns and not to determine the MW of the asphaltenes, due to the difference in complexity between the polymer standards and asphaltene's matrix. However, in our previous publications we have shown that HMW size distribution are primarily aggregate compounds, while LMW are "free" compounds, and MMW a mixture of "free" and aggregate compounds 34,36,37 .…”
Section: Methodsmentioning
confidence: 83%
“…Gel permeation chromatography (GPC) has been a recurrent tool for estimating the average molecular weights in polymeric feedstock. [27][28][29] Figure 2 provides an overview of the ample ranges of molecular weights and boiling points that some of the most common biomass-derived (Figure 2a) and plastic-derived (Figure 2b) fractions present, and it showcases the need for advanced characterization techniques that can elucidate even the heaviest polymeric fractions. Thermogravimetric techniques are also wellestablished for understanding the thermal behaviors of various samples (i.e., proximate analysis).…”
Section: Perspective Please Do Not Adjust Marginsmentioning
confidence: 99%